PENGARUH PERSEPSI KEPERCAYAAN, KEMUDAHAN DAN RESIKO TERHADAP MINAT DAN KEPUTUSAN PEMBELIAN MENGGUNAKAN METODE PEMBAYARAN SHOPEE PAYLATER PADA MAHASISWA UNIVERSITAS RIAU - ,, Rendra Wasnury, Eby Saputra , Gatot Wijayanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
In the digital lifestyle-first era, shopping has never been augmented, thanks to e- commerce and fintech. The high interest in shopping online encourages the emergence of businesses with the method of trading goods or services through online media called e-commerce. When you see the item you want on social media or in the market, you can buy it and have it delivered immediately with a few taps on your smartphone. Then, if you run out of cash, application users can even pay later using the BNPL method. This study aims to determine how much influence the aspects that influence buying interest and decisions, in this case the researcher uses the variables of trust, ease and risk as influencing variables. Primary data obtained from distributing questionnaires and supported by falsification of respondent's identity in order to validate the research results. This study used 105 students who used the paylater feature in the application as a research sample. Data processing techniques in this study include instrument testing, classical assumption testing, hypothesis testing, and path analysis as a flow of data testing and assisted by the SPSS version 25 application in data processing. The results of this study indicate that the variables of interest and purchase decisions have a positive and significant effect on trust, ease and risk. It can be concluded that the higher It can be interpreted that the more trust, ease and minimum risk, will increase interest so as to increase the decision to use the shopee paylater payment method in buying an item for Riau University students. Keywords: Perceived Trust, convenience, risk, interest, purchase decision, paylater.